Cytology diagnosis of metastatic clear cell renal cell carcinoma, synchronous to pancreas, and metachronous to thyroid and contralateral adrenal: Report of a case and literature review. Issue 2 (22nd October 2016) - Bokhari, Aqiba; Tiscornia‐Wasserman, Patricia G.
Abstract : Renal cell carcinoma metastases to pancreas, thyroid, and contralateral adrenal gland are decidedly uncommon. Clear cell renal cell carcinoma (CCRCC) is the most frequent subtype. Cytology diagnosis may be challenging. A 74‐year‐old male with remote history of vocal cord malignancy and hypertension presented with abdominal pain. Computed tomography (CT) revealed 8.4 cm left renal mass highly suspicious for renal cell carcinoma, a 1.8 cm mass within vessels near left adrenal and a 2.5 cm mass in pancreatic tail. Right pulmonary middle lobe showed two small nodules. Metastatic CCRCC was diagnosed on preoperative transgastric, endoscopic ultrasound guided fine‐needle aspiration cytology of pancreatic tail mass. Left radical nephrectomy and distal pancreatectomy and splenectomy confirmed CCRCC (pT3bNxM1), with metastases in adrenal and pancreatic tail. The 3p deletion identification in pancreatic tumor suggested CCRCC origin. Follow‐up positron emission tomography‐CT (PET‐CT) scan revealed left thyroid lower pole mass. Thyroid ultrasound showed three clustered 6 mm nodules in left mid pole. Ultrasound‐guided fine needle aspiration (US‐FNA) biopsies, 4‐month post‐nephrectomy, were consistent with metastatic renal cell carcinoma in lower, and atypia of undetermined significance in mid poles respectively. Left lobectomy and isthmus and pyramidal lobe resections confirmed metastatic renal cell carcinoma. One year post‐radical nephrectomy, contralateral adrenal lesion noted on PET‐CT was interpreted as metastatic CCRCC on CT‐guided core biopsy with touch imprints. Rapid on‐site evaluation was implemented, and immunoprofile typical of CCRCC substantiated cytomorphology at all three sites. Previously reported cases of renal cell carcinoma metastases to organs as in the described case are reviewed as well. Diagn. Cytopathol. 2017;45:161–167. © 2016 Wiley Periodicals, Inc.